Hubungan Pengetahuan Ibu Nifas Tentang Perawatan Luka Post SC Dengan Kejadian Infeksi Luka SC di Desa Multatuli Kec Natal Kab Mandailing Natal Tahun 2023 - Rizky Andriani; Isyos Sari Sembiring; Ernawati Napitupulu; Titin Suherni; Elnia Elnia (Calory Journal Medical Laboratory Journal, 2024)
BACKGROUND The exact incidence of infertility is not yet known with certainty, it varies greatly. Birth can occur in two ways, normal or natural (vaginal) and abnormal or delivery which is usually known as caesarean section. SC (Sectio Caesarea) is an artificial birth where the fetus is born through an incision in the abdominal wall and uterus, which can result in bleeding and incision wounds (Meo, 2021). In Indonesia, the number of caesarean sections increases along with the incidence of post-SC wound infections, where around 90% of post-cesarean section morbidity in the data obtained is caused by surgical wound infections. The incidence of caesarean sections (SC) is increasing every year, and according to the World Health Organization the standard for caesarean sections in a country is 5-10% of every newborn in the world (Hastutik, 2020).OBJECTIVE: To analyze the relationship between postpartum mothers' knowledge about post-SC wound care and the incidence of SC wound infections in Multatuli Village, Natal District, Mandailing Natal Regency in 2023. METHOD chi square test p value < 0.05 means H0 is rejected and Ha is accepted, the statistical test results show a significant relationship . RESULTS: There is a significant relationship between the knowledge of postpartum mothers regarding post-SC wound care and the incidence of SC wound infections. Suggestions are given for research and for research sites and for educational institutions regarding Post SC Wound Care